Mental health services for single homeless people. (March 2021) - Timms, Philip; Drife, Jenny
SUMMARY: Homelessness has long been associated with high rates of psychosis, alcohol and substance misuse, and personality disorder. However, psychiatric services in the UK have only recently engaged actively with homeless people. This article provides some background information about homelessness and mental illness and describes the elements of inclusion health and some of the models of service for homeless people that have been established over the past 30 years.